Verdi's La Traviata - Piave, Francesco Maria, 1810-1876 (Opera Journeys, 2005)
A comprehensive guide to Verdi's LA TRAVIATA, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 30 music highlight examples.
"Libretto by Francesco Maria Piave, after the novel, La Dame aux Camélias by Alexandre Dumas (fils)"--Page 11.
Keywords: Verdi, Giuseppe, -- 1813-1901. -- Traviata.; Traviata (Verdi, Giuseppe); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos